Designing resistance training programs - Fleck, Steven J. 1951-; Kraemer, William J. 1953- (Human Kinetics, 2014)
A guide to developing individualised training programmes for both serious athletes and fitness enthusiasts. Suitable for students, researchers and practitioners, it offers the information and tools to help readers evaluate resistance training programmes and better understand the context and efficacy of new data findings in this evolving field